Association of maternal Serum Selenium Binding protein and its effect on fetal outcomes in Pregnancy Induced Hypertensive Disorders: A case-control study. - Arshad, Sonya; Ahmed , Sadaf; Shershah Syed (International Journal of Endorsing Health Science Research, 2021)
Background: Pregnancy-induced hypertensive (PIH) disorder represented the primary cause of maternal and fetal morbidity and mortality. The cause of pre-eclampsia is unknown, but ischemic blood supply to the placenta stimulates the inflammatory process which leads to endothelial dysfunction and oxidative stress. Antioxidants like Selenium altered concentration involve in its pathogenesis. This study was proposed to find out the significance of Selenium as a biomarker in the pathophysiology of PIH disorders and its association with fetal outcomes. Methodology: This case-control study was conducted on 240 pregnant women, 20-40 weeks of gestation, divided into four groups equally. Normotensive control, investigational group 1 PIH, 2 Pre-eclamptic, and 3 Eclamptic. A structured questionnaire was administered and arterial blood pressure was measured and the blood sample was done for serum Selenium assessment through ELISA. A urine sample was collected and the level of proteinuria was assessed. Fetal wellbeing and signs of growth restriction were observed using ultrasound reports. Results: The mean age of the studied participants was 27.6 ± 5.3 years with the gestational age of 32.11 ± 4.56 weeks. The mean Serum Selenium levels (ng/ml) were significantly lower in investigational groups 67.93 ± 10.54 in PIH, 44.6 ± 13.19 in PE, and 36.38 ± 10.3 in Ec than 78.5 ± 8.2 control (p<0.05). The mean systolic, diastolic blood pressure and proteinuria were significantly high in case groups (p<0.05). Furthermore, we observed a significant inverse correlation of serum selenium with gestational age, systolic, diastolic blood pressure, proteinuria, fetal weight, and femur length in all four groups, whereas mainly positive significant correlation was elucidated with serum glutathione, PIH (r= 0.797, p<0.001), PE (r = 0.617, p>0.00), Ec (r=0.559, p=0.019) than control (r = 0.817, p<0.001). Conclusion: It is concluded that serum selenium level is significantly reduced in Pregnancy-induced hypertensive disorders and it has markedly affected maternal and fetal outcomes.